Perancangan Video Campaign Berbasis CGI sebagai Upaya Meningkatkan Brand Awareness pada Perusahaan Properti - Yahya Aladdin; Kusnadi Kusnadi; Rifqi Fahrudin (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
A campaign is a method for promoting products, but it does not do so directly. This study aims to create a campaign designed to enhance awareness through engaging video content. Prospective customers will be directed to more detailed product information on the Grand Taman Anggrek Suci website. Therefore, the campaign is designed to be both attractive and brief, to capture attention quickly. The goal is to help boost sales for Grand Taman Anggrek Suci. Additionally, this research focuses on problem-solving with a human-centered approach and requires innovative thinking. The research methodology used is Design Thinking, first introduced by John E. Arnold. The reference book for this research is Design Thinking for Strategic Innovation by Idris Moote (2013). The study utilizes several software tools, including 3D Blender and Adobe Premiere, to ensure the video achieves optimal and desired results. The final deliverables of this research include the Video Campaign and an Instagram account for its publication.